Addition–elimination versus Tishchenko reaction in the gas phase. (December 2014) - Wilenska, Beata; Swider, Pawel; Danikiewicz, Witold
<x xml:space="preserve">Abstract</x> Gas phase reactions of the substituted phenide ions with methyl formate have been studied. It was found that the results of these reactions depend mainly on the basicity of the phenide ion, which is related to the presence of the electron‐accepting or electron‐donating substituents in the benzene ring. It was shown that the phenide ions substituted with electron‐withdrawing groups react with methyl formate in the gas phase in a two‐step reaction. The first step that proceeds according to the typical addition–elimination mechanism results in the formation of the anion of the respective benzaldehyde derivative with the negative charge located either in the aldehyde group (acyl anion) or in the benzene ring (phenide anion) in position ortho to an aldehyde moiety. In the second step, the preliminary‐formed anion reacts with the second molecule of methyl formate yielding formally product of the second addition–elimination reaction. Theoretical calculations as well as collision induced dissociation spectra of the model compounds suggest that this reaction proceeds according to the Tishchenko reaction mechanism yielding the respective phthalide anion. According to our knowledge, this is the first example of the Tishchenko‐type reaction in the gas phase. Copyright © 2014 John Wiley & Sons, Ltd.